Pengaruh sudut twist drill terdahap kekasaran dan kebulatan pada proses pemesinan drilling - Nasution, Arya Rudi; Wahyudi, Fauzi S; Siregar, Chandra A; Affandi, Affandi; Fuadi, Zahrul (Universitas Muhammadiyah Jakarta, 2023)
Coolant and twist drill angle is one of the factors that affect the quality of the workpiece. Coolant selection and twist drill angle are useful for reducing hole roughness and increasing drill hole precision. In addition, the coolant must be easily degraded in the environment so that the environment is not polluted. An example of coconut oil is oil that can be degraded in the environment. This study aims to determine the effect of coconut oil (CO) and drill bit angle on the hole and hole precision obtained during the drilling process. In experimental testing, conventional drilling machines are used for test testing. the tests were carried out under various machining parameters, namely spindle rotation speed of 1100 rpm, drill bit angles of 130° and 135°. Based on these parameters, the spindle rotation speed of 1100 rpm and the drill bit angle of 135° is rougher than the drilling results for the spindle rotation speed of 1100 rpm and the drill bit angle of 130°. In addition, the roundness of the drilled holes for a spindle rotational speed of 1100 rpm and a drill bit angle of 130° is more precise than the spindle rotation speed of 1100 rpm and a drill bit angle of 135°.